PENGARUH CITRA MEREK DAN ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK HANDPHONE VIVO SMARTPHONE PADA PT SALIM SURYA PHONE DI SAMARINDA - Rijal Setiawan (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2020)
The background of this research is the sales of Vivo Smartphone that is not stable at PT Salim Surya Phone Samarinda. The sales decline was caused by the brand image and attribute products. There are some purposes of this study are to know and analyse the variable influences of brand image and attribute products to the purchasing decision of Vivo Smartphone at PT Salim Surya Phone Samarinda. And to know which variables have the dominant influences on the purchasing decision of these products. The research method that the researcher used is a quantitative research method. The sample of this study was 100 respondents with amount population. The technique that used is Incidental sampling Technique. The data collection technique is study of literature and field research that is questionnaire, observation, and interview. While the data analysis technique used multiple linear analysis. The conclusion of this study are the variable of brand image (X1) and attribute products (X2) simultaneously and partial significant effects on purchasing decision (X2) is to have a dominant influence on products purchasing decision of Vivo Smartphone at PT Salim Surya Phone Samarinda.